Development of a canva-based e-module on Sumbang 12 in the Budaya Alam Minangkabau (BAM) subject for grade V elementary school students - Yana Adawiyah; Zaka Hadikusuman Ramadan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This study aims to develop a Canva-based E-Module on the Sumbang 12 material of the Budaya Alam Minangkabau (BAM) subject for Grade V students. The study employed both quantitative and qualitative methods. It is a Research and Development (R&D) study using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Six validators validated the Canva-based E-Module across three aspects: content, language, and media. The content validation received a score of 96.71%, categorised as